2010
DOI: 10.1124/jpet.110.174904
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide Prodrug JS-K Is Effective against Non–Small-Cell Lung Cancer Cells In Vitro and In Vivo: Involvement of Reactive Oxygen Species

Abstract: Non-small-cell lung cancer is among the most common and deadly forms of human malignancies. Early detection is unusual, and there are no curative therapies in most cases. Diazeniumdiolate-based nitric oxide (NO)-releasing prodrugs are a growing class of promising NO-based therapeutics. Here, we show thatis a potent cytotoxic agent against a subset of human non-small-cell lung cancer cell lines both in vitro and as xenografts in mice. JS-K treatment led to 75% reduction in the growth of H1703 lung adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 38 publications
6
69
0
Order By: Relevance
“…Trx expression in these tumors is commonly associated with high proliferation index and inversely correlates with apoptosis [52, 53]. Of further note, it was shown that A549 cells display enhanced TrxR activity and high resistance to nitrosative stress [54, 55]. These previous observations together with the present study suggest the possibility that elevated activity of Trx/TrxR could promote lung cancer progression through their denitrosylase activity.…”
Section: Discussionsupporting
confidence: 74%
“…Trx expression in these tumors is commonly associated with high proliferation index and inversely correlates with apoptosis [52, 53]. Of further note, it was shown that A549 cells display enhanced TrxR activity and high resistance to nitrosative stress [54, 55]. These previous observations together with the present study suggest the possibility that elevated activity of Trx/TrxR could promote lung cancer progression through their denitrosylase activity.…”
Section: Discussionsupporting
confidence: 74%
“…While significant progress has been made in the last decade, the role of * NO/ * NO-related species remains poorly understood in chemotherapy and drug resistance. Here, we review the role of * NO/ S-nitrosothiols (sugar-SNAP) that resulted from enhanced uptake of saccharides in tumor cells and delivering * NO directly to tumor cells (34). Reynolds et al [29] have reported synthesis of polysaccharidebased dextran thiomers which contained covalently attached NOdonors.…”
Section: +mentioning
confidence: 99%
“…JS-K is active against human non-small cell lung cancer cells [34] and induces apoptosis in human multiple myeloma cells both in vitro and in vivo [35]. It was found that JS-K was activated following reactions with glutathione to produce * NO in vivo catalyzed by glutathione S-transferase [33].…”
Section: Becausementioning
confidence: 99%
“…O 2 -(2,4-dinitrophenyl)1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate] or JS-K (Figure 1), an arylated diazeniumdiolate has potent anti-leukemic activity in vitro and in vivo (10). In in vivo murine models, JS-K was also found to be effective against prostate cancer (10), hepatoma (11), multiple myeloma (12) and non-small cell lung cancer (13). JS-K also possesses anti-angiogenic activity both in vitro and in vivo (14).…”
Section: Introductionmentioning
confidence: 99%